2008
DOI: 10.1590/s0100-29452008000200022
|View full text |Cite
|
Sign up to set email alerts
|

Fenologia, produção e teor de antocianinas de cultivares de morangueiro em ambiente protegido

Abstract: RESUMO -A diversidade de cultivares de morangueiro exige estudos quanto à adaptação no local de cultivo. Por sua vez, a maior exigência do consumidor por produtos mais saudáveis requer informações a respeito das características nutracêuticas dos produtos. Este trabalho objetivou determinar as cultivares com maior adaptação ao cultivo protegido na região do Planalto Médio do Rio Grande do Sul, os teores de antocianinas, bem como a época de plantio que proporcionam maior produtividade. O experimento foi conduzid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
2
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 6 publications
1
5
2
11
Order By: Relevance
“…These results corroborate those of Calvete et al (2008) and Resend et al (2010), which both report cultivar Dover producing the highest number of noncommercial fruits, directly influencing the NFM. According to Howard and Albregts (1980) and Santos (2009), the cultivar Dover is known for producing small fruits and is therefore presumed to have genes related to smaller fruit size, with some degree of dominance.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results corroborate those of Calvete et al (2008) and Resend et al (2010), which both report cultivar Dover producing the highest number of noncommercial fruits, directly influencing the NFM. According to Howard and Albregts (1980) and Santos (2009), the cultivar Dover is known for producing small fruits and is therefore presumed to have genes related to smaller fruit size, with some degree of dominance.…”
Section: Resultssupporting
confidence: 91%
“…Studies focused on cultivar evaluation that have been carried out in Brazil have reported productivities of 607 g plant -1 (Calvete et al, 2008) and 840 g plant -1 (Resende et al, 2010) for cultivar Camarosa, 549 g plant -1 (Calvete et al, 2008) and 653 g plant -1 (Resende et al, 2010) for cultivar Dover, and 708 g plant -1 (Oliveira & Scivittaro, 2011) for cultivar Aromas, showing the high performance of these cultivars, as also evidenced by the original breeding programs (Camarosa: Voth, Shaw, & Bringhurst, 1994;Dover: Howard & Albregts, 1980, Aromas: Shaw, 1998. The existence of hybrids with production that is higher than the production shown by the cultivars in this trial and reported in the quoted literature indicates that at least some of the studied hybrid combinations have high productive potential.…”
Section: Resultsmentioning
confidence: 99%
“…The authors also reported considerable differences between the fruit weight of the same cultivar in both cities, indicating different behavior of genotypes between two production regions, since condition management were the same in both experiments. Calvete et al (2008), on experiment in conventional system in Passo Fundo, RS, has data in which 'Dover' presents as a cultivar with larger production on number of fruits, statically differentiating from 'Campinas', which does not differ from cultivars with lower production, in disagreement with this work found.…”
Section: Resultscontrasting
confidence: 60%
“…A interação dos fatores para produtividade por planta ocorreu por um aproveitamento melhor dos recursos de produção promovido pelo ambiente telado artesanal, gerando aumento da produção comercial e maior proteção aos frutos (Calvete et al, 2008 Nas plantas cultivadas em campo aberto a adição do biofertilizante elevou a produção por planta de 56,314 para 98,819 g planta -1 entre as plantas sem e com a dose ótima de 922 mL de biofertilizante (Figura 1A). Resende et al 2010 encontraram, no cultivo a campo, que a cultivar Oso Grande apresentou melhor desempenho com incremento de produção de 30,93, 31,65 e 51,12% em relação às cultivares Dover, Sweet Charlie e Camarosa, justificado pelo fato do ambiente protegido promover menores aeração e ventilação, reduzindo a polinização do morangueiro.…”
Section: Resultsunclassified